2017
DOI: 10.1080/09273948.2017.1291842
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Lipopolysaccharide (LPS) Preconditioning against Endotoxin-Induced Uveitis (EIU) in Rats is Associated with Overexpression of Interleukin-1 Receptor-Associated Kinase M (IRAK-M)

Abstract: Endotoxin tolerance has a protective effect against EIU, and upregulation of IRAK-M through TLR-signaling pathway is one of the most likely candidates to be involved in the observed phenomenon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Of the 49 included in vivo studies, 12 studies reported data from experiments performed using in vivo human model [ 45 , 50 60 ], 34 studies [ 29 , 32 , 36 41 , 43 , 61 – 85 ] used rodents (mice or rats), and the remaining three used sheep [ 44 ], cows [ 86 ] or pigs [ 42 ]. All included human studies (12 studies) used LPS administration with in vivo doses of 2–4 ng/kg.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 49 included in vivo studies, 12 studies reported data from experiments performed using in vivo human model [ 45 , 50 60 ], 34 studies [ 29 , 32 , 36 41 , 43 , 61 – 85 ] used rodents (mice or rats), and the remaining three used sheep [ 44 ], cows [ 86 ] or pigs [ 42 ]. All included human studies (12 studies) used LPS administration with in vivo doses of 2–4 ng/kg.…”
Section: Resultsmentioning
confidence: 99%
“…Of included studies, there were 20 studies (12 mouse studies and 8 human studies) in which two-challenge intervention was performed [ 29 , 36 , 38 , 39 , 42 45 , 51 , 52 , 54 , 55 , 58 – 64 , 86 ]; and nine studies made use of IRAK3 gene knockout or silencing [ 32 , 36 41 , 67 , 68 ]. Most studies (44 studies) measured outcomes at intervals ranging between 1h and 72h following the first challenge, while several studies measured outcomes at 5d [ 43 ], 7d [ 44 , 59 , 67 , 68 ], 10d [ 86 ], or 14d [ 42 ]. After the second challenge, outcomes of interest were measured between 2h and 24h.…”
Section: Resultsmentioning
confidence: 99%
“…Here, TLR4-signaling and its possible alteration via preconditioning might play an important role [22,23]. Inflammatory preconditioning has also been investigated in contexts of inflammation after stroke or spinal cord injury where neuroprotective effects have been shown [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The body becomes tolerant to subsequent exposure to a lethal dose of LPS and tissue damage caused by inflammatory reaction is significantly reduced; this phenomenon is called endotoxin tolerance (ET) [6]. Accumulating evidences [7,8] show that a low dose of LPS pretreatment can relieve the intraocular inflammation in EIU rats. This protective effect is associated with changes of PI3K/AKT pathway and upregulation of IRAK-M, which is mediated by TLR4 signaling pathway.…”
Section: Introductionmentioning
confidence: 99%